Arthralgia- the principal side effect in Breast Cancer Patients Receiving Aromatase Inhibitors and its management - Kotturu Saroja, V. Mohan Ram (Journal of Applied Pharmaceutical Science, 2017)
Breast cancer is the common cause of cancer death in women. In the adjuvant setting, Aromatase inhibitors (AIs) such as letrozole, anastrozole, and exemestane play an important role in treating postmenopausal women (PMW) with hormone receptor-positive breast cancer. Since estrogen endorses the growth of breast cancer cells, AI’s act by inhibiting aromatase enzyme which is involved in peripheral synthesis of estrogen in PMW. Standard duration of AI therapy is 5 years to achieve good prognosis but AI’s are principally associated with skeletal symptoms where arthralgia is the primary reason for early discontinuation. The purpose of the study was to assess the incidence of arthralgia in south Indian population and to conclude its management. The retrospective case review included 81 breast cancer patients with positive hormone receptor status, who were receiving adjuvant AI therapy. The Incidence of arthralgia was 49% in the AI treated group and it is high among young adults (50 vs. 65, p value= 0.0278) when compared to the elderly patients. The incidence of arthralgia in bisphosphonates treated AI group is less when compared to Non bisphosphonates group (P value = 0.0277). Hence bisphosphonates can be an initial choice of therapy in patients with AI induced arthralgia.
Keywords: Aromatase inhibitors, Bisphosphonates, Arthralgia, Breast cancer.